How Do I Rate Myself?” Self-Efficacy from the Teachers’ Point of View in Aviation Vocational School - Tiara Sylvia; Laila Rochmawati; Susi Diriyanti (Jurnal Ilmu Pendidikan, 2025)
This study investigates the factors influencing aviation vocational school instructors' self-efficacy and its effects on student engagement, classroom management, and instructional strategies. A sample of 100 participants was used to analyze the correlation between teacher self-efficacy and variables such as age, gender, position, additional assignments, highest degree of education, and institution. The impact of self-efficacy on supporting factors, specifically: a. the effectiveness of student engagement (ESE) and teacher self-efficacy: there is a substantial correlation between ESE and teacher self-efficacy, with ESE having a 98% influence on teacher self-efficacy; b. the effectiveness of classroom management (ECM) and teacher self-efficacy: a significant relationship is also observed between ECM and teacher self-efficacy, with ECM having a 98 percent impact on teacher self-efficacy; c. the effectiveness of instructional strategies (EIS) and teacher self-efficacy: a significant correlation exists between EIS and teacher self-efficacy, with EIS having a 98 percent influence on teacher self-efficacy. The findings demonstrate that the variables of age, position, education, and agency origin exert a substantial impact on the self-efficacy of teachers at aviation schools. Furthermore, elements such as student involvement, classroom management, and learning strategies are significant contributors to the enhancement of teacher self-efficacy within the context of an aviation vocational school